IMPLEMENTASI ASESMEN DIAGNOSTIK DALAM PEMBELAJARAN IPA PADA MASA PANDEMI COVID-19 DI SMP/MTS WILAYAH MENGANTI, GRESIK - Diki Firmanzah; Elok Sudibyo (PENSA: E-JURNAL PENDIDIKAN SAINS, 2021)
This research was conducted with the aim of knowing the design and implementation of diagnostic assessments in 3 junior high schools based on school quality categories. The research design used a qualitative descriptive. Subjects in this study were teachers in natural science subjects at 3 junior high schools in Menganti, Gresik. The selection of this school was based on the school quality category, namely SMP Negeri 29 Gresik with A accreditation, SMP Sunan Giri Menganti with A accreditation, and MTs Salafiyah Menganti Gresik with B accreditation. This research method used a qualitative descriptive method using a research instrument in the form of a questionnaire. on google form media. The data analysis technique in this study used namely data reduction, data presentation, and conclusion drawing. The results in this study are that all-Natural Science subject teachers in all these schools have implemented a diagnostic assessment before the learning process during the Covid -19pandemic and are in accordance with the rules of the Ministry of Education and Culture 2020. The design of diagnostic assessment carried out by teacher is in the form of test sheets and interviews. to students. The conclusion of this study is that the implementation and diagnostic design are not based on good quality schools, but depend on the teacher's understanding the importance of this assessment which makes science teachers in the 3 schools implement diagnostic assessments with the aim of helping students better understand the material and support achievement. learning objectives during the Covid -19 pandemic.